Soil chemical recovery and nutrient mobilization in post-mining land following application of rumen-based organic amendments under Cymbopogon nardus cultivation - Rusmini, Rusmini; Mudi, La; Abidin, Zainal; Sardianti, Andi Lelanovita; Suhartanto, Wiwin (Brawijaya University, 2026)
Post-mining soils are commonly characterized by high acidity, low nutrient availability, and elevated aluminum content, which can limit plant growth. This study evaluated changes in soil chemical properties of a post-mining soil and essential oil composition of citronella (Cymbopogon nardus) following the application of rumen-based organic amendments. Two citronella varieties, Variety A (the Pontianak variety) and Variety B (a local variety), established on post-coal mining land, were amended with organic amendments: BioMasta solid organic fertilizer (compost) and BioMasta liquid organic fertilizers. The solid fertilizer was applied at a rate of 20 t ha?¹ (approximately 1 kg plant?¹), and the liquid fertilizer was applied at a rate of 40 mL plant?¹ every two weeks for 90 days, resulting in six applications during the vegetative growth phase. A paired t-test was used to compare changes in soil properties and in the volatile compounds of citronella essential oil. The results showed that soil pH, organic carbon, total nitrogen, and available phosphorus. Significant differences in properties between the soil planted with citronella Variety A and that planted with citronella Variety B were observed for exchangeable aluminum, aluminum saturation, phosphorus availability, and organic carbon. The soil planted with citronella Variety B showed lower aluminum saturation and higher phosphorus availability than that planted with citronella Variety A. The essential oil composition of citronella also changed due to organic amendment application. Citronellal decreased, whereas ?-citronellol and nerol increased in both varieties.